How you can trade like a pro : breaking into options, futures, stocks, and ETFs - Potter, Sarah (McGraw-Hill, 2014)
"DO YOU WANT TO TAKE YOUR TRADING TO THE NEXT LEVEL?To earn a living as a trader, even part time, takes consistency. Most first-time investors find today's turbulent markets are anything but consistent. To keep from throwing your money away following obsolete tradingstrategies, you need a seasoned mentor like Sarah Potter to provide the latest insight, training, techniques, and action steps to become the trader you want to be. How You Can Trade Like a Pro holds the answer to fulfilling your dream of earning an income by trading. Written by an educator who now trades full time, this how-to book is unmatched in its clarity and to-the-point explanations. You will quickly develop a solid foundation of theory and professional techniques for tradingmultiple markets including options on stocks and ETFs as well as futures contracts. Unlike many nuts-and-bolts investing books, this holistic guide helps you through the technical and emotional process of trading, with Potter's real-life stories of transitioning to a full-time trader and her humorous "Trading Tips" comic strips. Best of all, you can start with a small amount of capital and be confident you have the same advantages as the pros. How You Can Trade Like a Pro provides expert coverage on: Understanding the risks and rewards of the market Avoiding the emotional pitfalls of trading Creating your own trading plan and watch lists Also includes: A simple tracking system to optimize trading performance Proven trading strategies explained step-by-step A variety of expert tools for accurately identifying market trends If you want to be a trader or just want to take back control of your fi nances, this guide shows you how to empower yourself with the trading routine that best fits you. Not only will you avoid costly brokerage fees, but you will have the satisfaction of growing your wealth your own way. Take the first step today and learn How YouCan Trade Like a Pro. TAKE CONTROL OF YOUR WEALTHHow You Can Trade Like a Pro is the cornerstoneguide to Sarah Potter's proven system for designing and implementing a professional-grade trading routine custom fit to your personality and goals. Whether you want to supplement your income or embark on a new career in trading, Potter has developed the ideal support structure to help everyone interested in growing capital transition into active traders focused on making a profit. PRAISE FOR HOW YOU CAN TRADE LIKE A PRO:"How You Can Trade Like a Pro is an excellent tool for anyone interested in learning how to trade. As experts in this industry, we know the greatest barrier to entry is the terminology. Sarah breaks down complicated topics into simple terms. This book will give new investors the con dence to trade on their own."--Liz Dierking and Jenny Andrews, The LIZ & JNY Show"Sarah Potter [offers] a fresh voice with essential information for active traders. Her comprehensive, inviting book is an informative A-to-Z compendium to helpnew traders find their path to profitable trading. TraderPlanet members vote her stories as some of the most popular on our site. We are sure you will find her writingto be engaging as well."--Lane J. Mendelsohn, Founder and President, TraderPlanet.com"--